Empirical Study: Quality of Islamic Banking In Medan City - Rahmayati Rahmayati (Universitas Muhammadiyah Surabaya, 2023)
However, the problem in Sharia Banking that affects the quality of Islamic banks is various things, including the absence of product differentiation and literation. Of course, this reality is a challenge for Islamic banks to improve and develop both internally and externally. This reality is the idea of the idea of making a new paradigm for Islamic banks as also conveyed in the Sharia Banking Development Road Map issued by the OJK for 2022-2025. This study aims to analyze the factors that affect the quality of Sharia Banking due to the current reality of Sharia Banking that does not support the quality in Islamic banks, so that it can be improved both in terms of products, community paradigms, and Islamic financial literacy which has increased, especially in Medan City by using variable testing techniques that affect the quality of Sharia Banking in Medan City. The results of this study show that the quality of Sharia Banking has an effect. The results of this study show that the quality of Sharia Banking has a significant effect on the quality of Islamic banks in Medan City from customer perceptions generated through product differentiation and literacy.